1996
DOI: 10.1159/000264284
|View full text |Cite
|
Sign up to set email alerts
|

Sirenomelia and Situs inversus: Case Report and Review of the Literature

Abstract: We report a case of sirenomelia of the symelia dipus type which is associated with complete situs inversus. Sirenomelia is difficult to diagnose prenatally because of a frequently associated oligohydramnios. Symelia dipus type adds to the difficulty of the diagnosis, since the bones of the thighs and legs are fully formed. In fact, a close examination of the cases of sirenomelia previously reported in the literature shows that a prenatal diagnosis was achieved only when the oligohydramnios was no more than mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 16 publications
1
13
1
Order By: Relevance
“…Sirenomelia has been associated with situs anomalies in only two previous reports [Kohler, 1972;Langer et al, 1996]. Langer et al described a sirenomelia of the symelia dipus type, with a situs inversus totalis of the thoracic and abdominal organs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sirenomelia has been associated with situs anomalies in only two previous reports [Kohler, 1972;Langer et al, 1996]. Langer et al described a sirenomelia of the symelia dipus type, with a situs inversus totalis of the thoracic and abdominal organs.…”
Section: Discussionmentioning
confidence: 99%
“…Situs inversus totalis has been reported in association with CD in only two prior instances, of which one consisted of sirenomelia [Langer et al, 1996;Bohring et al, 1999].…”
Section: Introductionmentioning
confidence: 99%
“…9 Stevenson et al 10 proposed the role of the persistent vitelline artery, which diverts blood from the abdominal aorta and caudal structures to the placenta, causing all distal visceral anomalies because of a vascular stealing phenomenon. Langer et al 11 have suggested a defect of the blastogenesis after the observation of a case of sirenomelia associated with "situs inversus." A deficit in the formation of the caudal region before the fourth week of gestation has been suggested by Duhamel, 4 who introduced the commonly used term "caudal regression syndrome."…”
Section: Discussionmentioning
confidence: 99%
“…A deficit in the formation of the caudal region prior to the fourth week of gestation has been suggested by Duhamel [2] and has led to the commonly used term ''Caudal regression syndrome.'' More recently, Langer et al suggested a defect of the blastogenesis following the observation of a case of sirenomelia associated with situs inversus [6].…”
Section: Discussionmentioning
confidence: 99%